Physico-chemical properties of Chernobyl lava and their destruction products. (September 2016) - Shiryaev, Andrey A.; Vlasova, Irina E.; Burakov, Boris E.; Ogorodnikov, Boris I.; Yapaskurt, Vasily O.; Averin, Alexey A.; Pakhnevich, Alexey V.; Zubavichus, Yan V.
Abstract: The paper commemorates 30th anniversary of severe nuclear accident at the 4th Unit of Chernobyl NPP. Results of the investigation of radioactive glassy lava-like materials formed as a result of the accident at their current state are presented. Complementary analytical methods: vibrational spectroscopy, XAFS, SEM, EBSD, X-ray tomography, provide new information about structure of the Chernobyl lava matrix and inclusions. Most of these techniques are applied to the lava samples for the first time and allow to derive consistent model of the lava and to resolve some of existing controversies. The glassy matrix of the lava is an anhydrous depolimerised metaluminous glass with signs of devitrification. Principal inclusions are (U, Zr)O2−x and (Zr, U)O2−x solid solutions with tetragonal and monoclinic structures, UO2 and U-rich zircon. Cracks around large inclusions are observed; some of them could be caused by volume expansion during tetragonal to monoclinic transition in zirconia. The lava accumulations are characterized by different stability against spontaneous destruction, with the pumice-like lava being the least stable, generating radioactive aerosols and particles with sizes up to 250 μm. Highlights: Current state of Chernobyl lava is studied using vibrational spectroscopy, XAFS, SEM, EBSD, X-ray tomography. The glassy matrix of the lava is an anhydrous depolimerised metaluminous glass with signs of devitrification. Principal inclusions are (U, Zr)O2− x and (Zr, U)O2− x with tetragonal and monoclinic structures, UO2 and U-rich zircon. Cracks around large inclusions could be caused by volume expansion in zirconia due to tetragonal to monoclinic transition. The pumice-like lava is the least stable type of lava, generating radioactive particles with sizes up to 250 µm.